Penatalaksanaan Restenosis Nasofarin Menggunakan Obturator Nasofaringeal - Eka Seftiana Indah Sari (Jurnal Kedokteran Gigi Terpadu, 2020)
Introduction: Nasopharyngeal stenosis (NPS) is a very rare condition that is characterized by the obstruction of the nasopharynx by submucosal fibrotic tissue from the soft palate and posterior pahrynx. NPS has been reported as a complication of infectious diseases. NPS is frequently iatrogenic and caused by oropharyngeal surgeries. Case Report : A twenty eight years old female patient arrived at clinic with complaints of nasal obstruction, swallowing difficulty. She had  history of pharyngeal surgery. Conclusion: Nasopharyngeal stenosis is difficult to correct. Multiple surgeries may be required to relieve the obstruction. Standard operative techniques using the lateral pharyngeal flap and transpalatal or endoscopic intranasal approach were adapted to the clinical situation. Prolonged use of nasal stents is mandatory to produce a nasopharyngeal opening.